2021
DOI: 10.3390/nano11112784
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Covalently Functionalized with Peptides Mapped on Vitronectin and BMP-2 for Bone Tissue Engineering

Abstract: Worldwide, over 20 million patients suffer from bone disorders annually. Bone scaffolds are designed to integrate into host tissue without causing adverse reactions. Recently, chitosan, an easily available natural polymer, has been considered a suitable scaffold for bone tissue growth as it is a biocompatible, biodegradable, and non-toxic material with antimicrobial activity and osteoinductive capacity. In this work, chitosan was covalently and selectively biofunctionalized with two suitably designed bioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In order to improve cell interaction with bioceramic surfaces, we have realized a surface modification of the MnGC with a BMP-2 mimetic peptide. This peptide, reproducing the sequence 48-69 of the BMP-2 protein, covalently linked to a chitosan porous scaffold [40], has shown improved h-osteoblast adhesion, proliferation, and calcium deposition. Usually, materials modified with the inclusion or grafting of bioactive molecules are defined as bioactive materials because they interact with cells using the biochemical cell language; consequently, we are formulating a bioactive bioceramic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve cell interaction with bioceramic surfaces, we have realized a surface modification of the MnGC with a BMP-2 mimetic peptide. This peptide, reproducing the sequence 48-69 of the BMP-2 protein, covalently linked to a chitosan porous scaffold [40], has shown improved h-osteoblast adhesion, proliferation, and calcium deposition. Usually, materials modified with the inclusion or grafting of bioactive molecules are defined as bioactive materials because they interact with cells using the biochemical cell language; consequently, we are formulating a bioactive bioceramic.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to further increase Mn-containing scaffold potentiality in bone tissue engineering, a selective and specific covalent functionalization [37,38] of Mn-containing bioactive glass (composition: Na 2 O-K 2 O-MgO-MnO-CaO-CaF 2 -P 2 O 5 -SiO 2 , named MnGC) with a bioactive peptide was performed. The anchored bioactive sequence is a BMP-2mimicking peptide (sequence 48-69 of BMP-2 wrist epitope) that has been proven to guide osteogenic differentiation of Mesenchymal Stem Cells [39] and promote h-osteoblasts' proliferation; calcium deposition; and gene expression of Runx2, Vitronectin, and Sparc when conjugated to a porous chitosan scaffold [40]. The present study demonstrated that the combined modification of both bioactive glass-ceramic composition and BMP-2mimicking peptide (here named BMP_aldehyde) enrichment could act synergistically to improve bone biomaterial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Different delivery systems have been used to obtain a slow, controlled release of active molecules. Protection of the active molecule can be done by inclusion in carriers [72] or fixating them to the surface of the implant [73]. Biocompatibility is one of the most important features of the carriers.…”
Section: Growth Factor Delivery Systemsmentioning
confidence: 99%
“…These bionic-inspired biomaterials, such as chitosan films functionalized with bioactive molecules, exhibit improved properties that mimic the natural extracellular matrix [ 8 ]. They provide an optimal microenvironment for cell adhesion, proliferation, and differentiation, promoting bionic-like tissue scaffolds that closely mimic the native and have been used for bone [ 9 ], skin [ 10 ], vascular [ 11 ] and nerve [ 12 ] regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Among different CS surface modifications, peptides derived from extracellular matrix (ECM) proteins have been generally probed [ 13 ]. Some studies have used specific motifs of ECM proteins to drive a desired cellular response [ 9 , 14 ]. However, regardless of CS’s potential application in tissue engineering, functionalization with arginyl–glycyl–aspartic acid (RGD) peptides and RGD derivatives are the most used bioactive motif [ 13 ].…”
Section: Introductionmentioning
confidence: 99%